The Presence of Holy Verses on Social Media: Examining the Influence of Muslim Influencers on Gen Z’s Religiosity through a Qur’anic Lens: Ayat-Ayat Suci di Media Sosial: Pengaruh Influencer Muslim terhadap Religiositas Generasi Z Perspektif Al-Qur’an - Ketrin Iryani; Abdul Fatah (Takwil: Journal of Quran and Hadith Studies, 2025)
The transition and acceleration of technology have opened new portals in the fields of information and communication. This includes aspects of information in the social and religious fields. This transition creates a new horizon that must be included in the rapid flow of technology. Therefore, the distribution of religious messages through da'wah needs to be reconstructed so that the audience still gets fundamental implications. This study aims to see how the da'wah patterns of muslim influencers on social media can still influence the religious attitudes of generation Z in the era of disruption. Not stopping there, the study also touches on the message in Q. S. An-Nahl [16]: 125 through hermeneutic studies by Imam At-Thabari, Imam Al-Razy, Sayyid Qutb, Buya Hamka and Prof. Quraish Shihab as a guide to the ideal da'wah method for da'i and ulama in conveying their da'wah messages. Through qualitative methods, the study was designed using a library study approach. The findings of this study are that the da'wah method contained in Q. S. An-Nahl [16]: 125 is able to provide an expansive effect on the da'wah messages conveyed by religious influencers through social media. Three methods that comprehensively influence the da'wah carried out are the bil hikmah method (verses of the Koran), the bil mau'idhoh hasanah method (good advice) and the bil mujjadallah method (discussion, debate, dialogue). By using these three methods the audience will be more cooperative in accepting Islamic teachings